2020
DOI: 10.3171/2019.4.jns183443
|View full text |Cite
|
Sign up to set email alerts
|

The benefit and risk of stereotactic radiosurgery for prolactinomas: an international multicenter cohort study

Abstract: OBJECTIVEThe most common functioning pituitary adenoma is prolactinoma. Patients with medically refractory or residual/recurrent tumors that are not amenable to resection can be treated with stereotactic radiosurgery (SRS). The aim of this multicenter study was to evaluate the role of SRS for treating prolactinomas.METHODSThis retrospective study included prolactinomas treated with SRS between 1997 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…The probability of obtaining normalization of remission is, in fact, generally lower than 50%. Interestingly, the remission rate between the larger multicenter studies by Hung et al is similar to that reported in smaller series [ 49 ]. The probability of normalizing PRL levels by combining GK and dopamine agonists approaches 50–70% at five years [ 39 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The probability of obtaining normalization of remission is, in fact, generally lower than 50%. Interestingly, the remission rate between the larger multicenter studies by Hung et al is similar to that reported in smaller series [ 49 ]. The probability of normalizing PRL levels by combining GK and dopamine agonists approaches 50–70% at five years [ 39 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 83%
“…Only four studies on GK treatment for prolactinomas were included in this systematic review and meta-analysis ( Table 4 ) [ 48 , 49 , 50 , 51 ]. Typically such patients have larger and regionally invasive tumors with PRL levels that indicate cavernous sinus invasion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few patients developed radiosurgery-related hypopituitarism. Hong and colleagues reported on 289 patients with prolactinomas treated with GKS at ten international centers [35]; the endocrine remission rates were 28%, 41%, and 54% at 3, 5, and 8 years, respectively, after SRS. In that study, however, 25% of all patients reported new treatment-related hormonal deficiencies and 3% of all patients developed visual complications related to SRS.…”
Section: Discussionmentioning
confidence: 99%